Pengaruh Penambahan Probiotik Mix Culture Pada Fermentasi Anaerob Kulit Kopi Terhadap Kadungan Serat Kasar, Dan Protein Kasar - Mohamad Haris Septian; lilis Hartati; Rahma Wulan Idayanti; ismiana Kholifatun (Fakultas Pertanian Universitas Majalengka, 2022)
This research aim to determine the effect of addition probiotic mixculture on the anaerobic fermentation of coffee peel on the content of dry matter, crude fiber, and crude protein. This research conducted by experimentally using a Complete Randomized Design (CRD) with 4 treatments and 5 repeats. The treatment was P1 (coffee peel + 3% molasses), P2 (coffee peel + 3% molasses + 0.5% Heryaki probiotic), P3 (coffee peel + 3% molasses + 1% Heryaki probiotic), P4 (coffee peel + 3% molasses + 1.5% Heryaki probiotic). The results showed that the addition of probiotic mix culture had no significant effect (P>0.05) on crude fiber and crude protein. The crude fiber (15.738%-17.714%) and crude protein (10.676%-12.019%). The conclusion of this study was that the addition of mix culture probiotics on anaerobic fermentation of coffee peel did not affect the crude fiber and crude protein content.